EVA Discipline Getting Hotter at HARSCO Corporation - Choudhary, Himanshu; Sharma, Vandana (Indian Journal of Finance, 2010)
EVA is an acronym for Economic Value Added. It helps in measuring the corporate performance. EVA is not only a measure of performance, but also a framework that helps decision makers in an organization to bring in organizational change. It helps in providing complete financial management and incentive compensation system that helps in improvement of the professional lives of everyone in an organization by making them more empowered. EVA stands as a unique tool amongst most others because it includes a charge against profit for the cost of the entire capital that a company employs. This helps the management in producing much more wealth for shareholders, customers, and their own selves.